FACTORS AFFECTING CAREER CHOICE AMONG UNDERGRADUATE STUDENTS IN UNIVERSITY OF ADEN (Journal of Technology and Operations Management, 2017)
One of the critical aspects of an individual’s life is career choice as this will determine the role pattern needed to be played by the individual in the society in the future, and it is one of the important processes in life. This study aims to investigate the factors influencing the career choice of the students. This study focused on undergraduate students in the University of Aden. Undergraduate students were chosen because right upon graduation, they are the ones who will be deciding on their career choices. The findings of the study largely supported the hypothesized relationships proposed in the theoretical model and showed that the family, self-efficacy and economic considerations exerted significant influence on the choice of a career among students. Moreover, the results showed that the influence of family, self-efficacy and economic considerations was positive on career choices. To investigating student’s career choice that is affected by other important factors, further studies are strongly recommended.